2007
DOI: 10.1007/s10557-007-6037-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen Peroxide in Human Internal Thoracic Arteries: Role of Potassium Channels, Nitric Oxide and Cyclooxygenase Products

Abstract: The findings of the present study suggested that H(2)O(2)-induced relaxation responses in human ITA were neither dependant on the endothelium nor blocked by NOS inhibition but they rather seem to depend on the activation of voltage-dependent potassium channels and COX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In contrast, Nacitarhan et al. [62] studied internal thoracic artery rings and found that authentic H 2 O 2 produced dose‐dependent relaxations that were blunted by 4‐aminopyridine, a voltage‐dependent potassium channel blocker. These contradictory results may reflect differences in the vascular beds and vasodilatory stimuli being studied.…”
Section: Role Of H2o2 In Endothelial Function In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Nacitarhan et al. [62] studied internal thoracic artery rings and found that authentic H 2 O 2 produced dose‐dependent relaxations that were blunted by 4‐aminopyridine, a voltage‐dependent potassium channel blocker. These contradictory results may reflect differences in the vascular beds and vasodilatory stimuli being studied.…”
Section: Role Of H2o2 In Endothelial Function In Humansmentioning
confidence: 99%
“…Although some reports describe H 2 O 2 as an EDHF in humans [53,58], others have offered conflicting evidence regarding the role of H 2 O 2 in mediating endothelium‐dependent vasodilation [12,30,32,44,53,57,62,69]. Hamilton et al.…”
Section: Role Of H2o2 In Endothelial Function In Humansmentioning
confidence: 99%
See 1 more Smart Citation